2006
DOI: 10.1007/s11548-006-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Centerline Extraction in 3D MR Angiograms for Phase Contrast MRI Blood Flow Measurement

Abstract: The accuracy of 2D phase contrast (PC) magnetic resonance angiography (MRA) depends on the alignment between the vessels and the imaging plane. PC MRA imaging of blood flow is challenging when the flow in several vessels is to be evaluated with one acquisition. For this purpose, semiautomatic determination of the plane most perpendicular to several vessels is proposed based on centerlines extracted from 3D MRA. Arterial centerlines are extracted from 3D MRA based on iterative estimation-prediction, multi-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, it should be used cautiously and not as the only indicator for rupture risk assessment. Other geometric indices such as wall thickness [14,21], surface curvatures [13,14], volume and surface area [14], thrombus volume [15], etc., should be accounted for to increase the accuracy of this estimation. Fillinger et al [29] also report on the influence of geometric variables in the classification of ruptured and unruptured AAAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be used cautiously and not as the only indicator for rupture risk assessment. Other geometric indices such as wall thickness [14,21], surface curvatures [13,14], volume and surface area [14], thrombus volume [15], etc., should be accounted for to increase the accuracy of this estimation. Fillinger et al [29] also report on the influence of geometric variables in the classification of ruptured and unruptured AAAs.…”
Section: Discussionmentioning
confidence: 99%
“…This method requires two assumptions that are not always valid: (i) that the intensities along the centerline follow a Gaussian distribution and (ii) that they follow the same (Gaussian) distribution. Conversely, Hoyos et al [15] applied moments of inertia to predict the projection of the centerline iteratively. The results are superior on cases with adequate contrast mixing and small data sizes, but the method has a similar disadvantage to the Hessian matrix based solution.…”
Section: Introductionmentioning
confidence: 99%
“…This method requires two assumptions that are not always valid: one is that the intensities along the centerline follow a Gaussian distribution and the other is that they follow the same distribution. Hoyos et al [14] applied moments of inertia to predict the projection of the centerline iteratively. The results are good on cases with good contrast and small sizes.…”
Section: Discussionmentioning
confidence: 99%
“…A volume of interest (VOI) and a point within the vessel are first interactively determined. The vessel central axis is then automatically extracted by an extensible-skeleton method [12,13]. Vessel boundaries are subsequently detected in planes locally orthogonal to the centerline, using an adaptive iso-contour method.…”
Section: Methodsmentioning
confidence: 99%
“…The 50% iso-value was also used in CE-MRA [5,6,18]. However, our previous experience [13] showed that an iso-value of 45% leads to better results in CE-MRA images. This value was fixed during all the experimentation.…”
Section: Vessel Boundary Detection Via Adaptive Iso-contoursmentioning
confidence: 99%